Movement-induced heart rate changes in epileptic and non-epileptic seizures Alterações da frequência cardíaca induzidas pelo movimento em crises epilépticas e não-epilépticas - Gisele R. de Oliveira; Francisco de A.A. Gondim; Edward R. Hogan; Francisco H. Rola (Arquivos de Neuro-Psiquiatria)
Heart rate changes are common in epileptic and non-epileptic seizures. Previous studies have not adequately assessed the contribution of motor activity on these changes nor have evaluated them during prolonged monitoring. We retrospectively evaluated 143 seizures and auras from 76 patients admitted for video EEG monitoring. The events were classified according to the degree of ictal motor activity (severe, moderate and mild/absent) in: severe epileptic (SE, N=17), severe non-epileptic (SNE, N=6), moderate epileptic (ME, N=28), moderate non-epileptic (MNE, N=11), mild epileptic (mE, N=35), mild non-epileptic (mNE, N=33) and mild aura (aura, N=13). Heart rate increased in the ictal period in severe epileptic, severe non-epileptic, moderate epileptic and mild epileptic events (p<0.05). Heart rate returned to baseline levels during the post ictal phase in severe non-epileptic seizures but not in severe epileptic patients. Aura events had a higher baseline heart rate. A cut-off of 20% heart rate increase may distinguish moderate epileptic and mild epileptic events lasting more than 30 seconds. In epileptic seizures with mild/absent motor activity, the magnitude of heart rate increase is proportional to the event duration. Heart rate analysis in seizures with different degrees of movement during the ictal phase can help to distinguish epileptic from non-epileptic events. Alterações da frequência cardíaca são comuns em crises epilépticas e não-epilépticas. Estudos prévios não avaliaram adequadamente a contribuição da atividade motora nas alterações da frequência cardíaca, e as crises não foram estudadas durante monitoração prolongada. No presente estudo avaliamos retrospectivamente 143 crises de 76 pacientes admitidos para monitoração com vídeo-EEG no Hospital da Universidade de Saint Louis. As crises foram classificadas de acordo com o grau de atividade motora (severa, moderada e leve/ausente) em: epiléptica grave (EG, N=17), não-epiléptica grave (NEG, N=6), epiléptica moderada (EM, N=28), não epiléptica moderada (NEM, N=11), epiléptica leve (EL, N=35), não-epiléptica leve (NEL, N=33), e aura, N=13. A frequência cardíaca aumentou no período ictal nas crises epilépticas graves, não epilépticas graves, epilépticas moderadas, epilépticas leves (p<0,05). A frequência cardíaca apresentou tendência a retornar aos níveis basais durante o período pós ictal nas crises não epilépticas graves, mas não nas crises epilépticas graves. As auras apresentaram frequência cardíaca basal aumentada. Um limiar de 20% no aumento da frequência cardíaca pode diferenciar eventos epilépticos moderados de eventos epilépticos leves com duração maior que 30 segundos. Em crises epilépticas com atividade motora leve ou ausente, a magnitude do aumento da frequência cardíaca é proporcional à duração do evento. A análise da frequência cardíaca em crises com diferentes quantidades de movimento na fase ictal podem ajudar na diferenciação de crises epilépticas de não epilépticas.